P97 Post-liver reperfusion hepatic vein portal gradient pressure measurement and the risk of graft dysfunction in whole liver transplantation. (16th November 2010) - El-Ghazaly Harb, S; Bartlett, A; Vilca-Melendez, H; Rela, M; Heaton, N
Abstract : Introduction: "Small for size liver syndrome" is relatively uncommon after whole liver transplantation. Portal hyperperfusion is thought to damage the hepatic microvasculature, and drive Small for size liver syndrome. Post-perfusion portal venous pressure (PVP) may be an indirect reflection of sinusoidal injury. Donor Risk Index (DRI) can be utilised to assess the quality of the graft, with those having a DRI>1.7 considered as marginal1 . This study looked at the association of portal pressure and graft quality in a whole liver transplant setting. Method: 50 adult patients who underwent liver transplantation underwent portal venous pressure measurements by direct pressure transduction during surgery. Central venous pressure was recorded at the same time points to be used to derive the Hepatic Venous Portal Gradient (HVPG) (HVPG=PVP-CVP). DRI was calculated for all the grafts used. The degree of fatty infiltration (%) was assessed on post-perfusion biopsies. Graft function was monitored post-operatively by recording INR (peak and days 1, 2, 3, 5 and 7), lactate (peak level and day 1 and 2) serum AST (peak and days 1, 2, 3 and 7) and serum bilirubin (days 1, 5 and 7). The presence of ascites, jaundice and coagulopathy were documented. Ascitic drain loss (ml/day) was recorded up to the time of drain removal. Results: A statistically significant correlation was found between PVP and DRI (p<0.05) (Abstract P97 Figure 1 ). This was supported by higher mean and median values of PVP in the group receiving grafts with a DRI>1.7 n=22) (Abstract P97 Figure 2 ). Patients in this group had a mean PVP of 15 (±2.976) mm Hg and a median of 14 mm Hg (range: 8–22), in contrast to those receiving grafts of DRI<1.7 (n=28) who had a PVP mean of 13.89 (±5.513) mm Hg and a median of 12.5 mm Hg (range: 6–34). No statistically significant correlation could be found between PVP and the degree of fatty infiltration. Post-perfusion HVPG had a significant correlation (p<0.1) with increased ascitic drainage on day 7. Conclusion: The HVPG should be evaluated as a tool for assessment of portal pressure post-reperfusion, particularly in patients transplanted with a high DRI, to predict morbidity post-transplant.